2008
DOI: 10.1002/ijc.23379
|View full text |Cite
|
Sign up to set email alerts
|

The hTAFII68‐TEC fusion protein functions as a strong transcriptional activator

Abstract: Human extraskeletal myxoid chondrosarcoma (EMC) is caused by a chromosomal translocation that involves TEC (translocated in extraskeletal myxoid chondrosarcoma), and either EWS (Ewing's sarcoma) or hTAF II 68 (human TATA-binding proteinassociated factor II 68), which generates EWS-TEC or hTAF II 68-TEC fusion proteins, respectively. Although there has been a great deal of progress in characterizing EWS-TEC, there is relatively little known about the biological function of hTAF II 68-TEC. We have examined the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 31 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…Both EWSR1-NR4A3 and TAF15-NR4A3 fusion proteins have been shown to be strong transcriptional activators. [23, 24]…”
Section: Discussionmentioning
confidence: 99%
“…Both EWSR1-NR4A3 and TAF15-NR4A3 fusion proteins have been shown to be strong transcriptional activators. [23, 24]…”
Section: Discussionmentioning
confidence: 99%
“…The EWSR1-NR4A3 fusion protein is thought to function as a potent transcriptional activator for NR4A3 -target genes [85, 86]. It has also been shown that the TAF15-NR4A3 fusion protein functions a strong transcriptional activator [87]. It is unclear whether the fusion transcript type is associated with particular morphological features or clinical outcome.…”
Section: Extraskeletal Myxoid Chondrosarcomamentioning
confidence: 99%
“…The pCMV‐Tag2A/TFG‐TEC, pCMV‐Tag2A/TFG (NTD), pCMV‐Tag2A/TEC, and pCMV‐Tag2A/TFG‐TEC (AAAA) expression plasmids have been described previously . To generate the pEnoβ‐Luc reporter plasmid, the human β ‐ enolase promoter (nucleotides −787 to +79 relative to the start of transcription; Figure ) was amplified from human genomic DNA by PCR using the following primers: hEnoβ‐787(s), 5′‐GATCGGTACCACAAAAGGCCACCCGTCC‐3′ (KpnI site underlined) and hEnoβ+79(as), 5′‐GATCCTCGAGCTGGAAGATTCACCCGAC‐3′ (XhoI site underlined).…”
Section: Methodsmentioning
confidence: 99%